Robert E. Lucas Jr.'s Collected Papers on Monetary Theory - Sargent, Thomas J. (Journal of Economic Literature, 2015)
This paper is a critical review of and a reader's guide to a collection of papers by Robert E. Lucas, Jr. about fruitful ways of using general equilibrium theories to understand measured economic aggregates. These beautifully written and wisely argued papers integrated macroeconomics, microeconomics, finance, and econometrics in ways that restructured big parts of macroeconomic research. (JEL A31, E00, E13, E50)